2006
DOI: 10.1124/jpet.105.097972
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Modulates Aromatic l-Amino Acid Decarboxylase Activity in Mouse Striatum

Abstract: Clozapine is efficacious for treating dopaminergic psychosis in Parkinson's disease and ameliorates L-DOPA-induced motor complications. Based on its pharmacology and reported enhancing effects on dopamine metabolism and tyrosine hydroxylase activity, we investigated whether it could modulate the activity of aromatic L-amino acid decarboxylase (AAAD), the second enzyme for the biosynthesis of catecholamines and indoleamines. A single dose of clozapine increased AAAD activity of striatum in a dose-and time-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Similar responses to dopamine receptor ligands have also been observed in various rodent brain regions (Zhu et al, 1992(Zhu et al, , 1993Hadjiconstantinou et al, 1993;Cho et al, 1997Cho et al, , 1999Neff et al, 2006). Regulation of AADC by serotonergic receptors (Neff et al, 2006) and Nmethyl-D-aspartate (NMDA) glutamatergic receptors (Hadjiconstantinou et al, 1995;Fisher et al, 1998) has also been reported. There is also some evidence for AADC regulation associated with systemic lupus erythematosus (Bengtsson et al, 2016), Parkinson' disease (Gjedde et al, 1993), and schizophrenia (Reith et al, 1994).…”
Section: Vertebrate Trace Aminessupporting
confidence: 58%
See 1 more Smart Citation
“…Similar responses to dopamine receptor ligands have also been observed in various rodent brain regions (Zhu et al, 1992(Zhu et al, , 1993Hadjiconstantinou et al, 1993;Cho et al, 1997Cho et al, , 1999Neff et al, 2006). Regulation of AADC by serotonergic receptors (Neff et al, 2006) and Nmethyl-D-aspartate (NMDA) glutamatergic receptors (Hadjiconstantinou et al, 1995;Fisher et al, 1998) has also been reported. There is also some evidence for AADC regulation associated with systemic lupus erythematosus (Bengtsson et al, 2016), Parkinson' disease (Gjedde et al, 1993), and schizophrenia (Reith et al, 1994).…”
Section: Vertebrate Trace Aminessupporting
confidence: 58%
“…In contrast, D1R agonists decrease both basal and lightinduced AADC activity (Rossetti et al, 1990). Similar responses to dopamine receptor ligands have also been observed in various rodent brain regions (Zhu et al, 1992(Zhu et al, , 1993Hadjiconstantinou et al, 1993;Cho et al, 1997Cho et al, , 1999Neff et al, 2006). Regulation of AADC by serotonergic receptors (Neff et al, 2006) and Nmethyl-D-aspartate (NMDA) glutamatergic receptors (Hadjiconstantinou et al, 1995;Fisher et al, 1998) has also been reported.…”
Section: Vertebrate Trace Aminesmentioning
confidence: 57%
“…Even though the P2/P1 ratio did not differ between VEH, L-TYR 62.5–125 μM and D-TYR 250 μM, this still raises the possibility of some carryover effects from P1 to P2. Pharmacologically induced acute activation of striatal TH typically ceases within 60 min of drug administration and does not affect the amount of TH protein for at least 6 h (Neff et al., 2006). In most studies of DA efflux, DA terminals appear to be fully recovered 60 min after cessation of an initial stimulus (Michael et al, 1987;Ripley et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We applied this approach to the medial prefrontal cortex (MPFC) and striatum (Brodnik et al, 2012) and postulated that as the concentration of L-TYR increased, DOPA levels would initially increase and then plateau due to inhibition of TH by L-TYR (Lloyd and Kaufman, 1974;Quinsey et al, 1998;Ribeiro et al, 1992), or by the end-product DA, given that inhibition of AADC by NSD-1015 remains incomplete (Neff et al, 2006). We were surprised, however, that in striatum increasing concentrations of L-TYR (62.5 – 1000 μM) incrementally elevated DOPA levels without evidence of inhibition (Brodnik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A TAAR1 agonist has been shown to have antipsychotic activity in animal models and is currently in clinical testing (Revel et al, 2013). DDC expression and activity are altered by APD administration, including clozapine, in rodents, suggesting that it could be relevant to response to APD treatment (Neff et al, 2006). DDC has been reported to be regulated by immediate and delayed mechanisms involving enzyme activation and gene expression induction (Neff et al, 2000).…”
Section: Ddc and Trace Aminesmentioning
confidence: 99%